Development and application of cathodic vacuum arc plasma for nanostructured and nanocomposite film deposition - M. Medhisuwakul (2018)
A cathodic vacuum arc plasma (CVAP) system was constructed at Chiang Mai University to be used for the deposition of nanostructured and nanocomposite thin films. Various CVAP sources were developed, such as with a single or dual-rod cathode. A range of features were implemented including "triggerless" arc initiation, macroparticle filters, and negative substrate bias, which can be pulsed. In our experiments, various kinds of conductive materials were used as cathode in modes of single- or multi-element film deposition. The film deposition could be done under several types of gas atmospheres with various pressures. These technical developments allowed us to produce diverse types of thin and nanostructured films. Examples of applications include Mo-containing tetrahedral amorphous carbon films, diamond-like carbon (DLC) films, nano-structured carbon films and C-Mo nanocomposite films, C-Ti and C-Pt hybrid films, Ti-nitride films, hybrid Ti-Ni films, etc. The films were applied to wafers used in microelectronics, and to components in fuel cells. © 2012 Elsevier B.V.